2012
DOI: 10.1589/jpts.24.1103
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Activity of Abductor Hallucis and Navicular Drop in the One-leg Standing Position

Abstract: Abstract. [Purpose] This study examined whether abductor hallucis (AH) activity in the one-leg-standing position can be used to predict the navicular drop (ND) when it is or is not actively supporting the medial longitudinal arch.[Subjects] Forty healthy subjects without foot or ankle problems were recruited.[Methods] For all subjects, the ND was measured as the difference in navicular height between the subtalar joint resting (STJR) and subtalar joint neutral (STJN) positions while standing. AH activity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…e abductor hallucis muscle has been gaining prominence in the most recent publications on plantar pain [10,11]. It is a superficial, triangular, flat, bipenniform muscle that fills the foot medial arch and is responsible for sustaining the arch and hallux abduction and flexion [12,13]. e muscle originates from flexor retinaculum, medial process of the calcaneus tuberosity, and intermuscular septum between itself and flexor hallucis brevis; the insertion is into the medial aspect of the proximal hallux phalanx, the collateral ligament of the proximal metatarsophalangeal joint, and the medial sesamoid bone [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…e abductor hallucis muscle has been gaining prominence in the most recent publications on plantar pain [10,11]. It is a superficial, triangular, flat, bipenniform muscle that fills the foot medial arch and is responsible for sustaining the arch and hallux abduction and flexion [12,13]. e muscle originates from flexor retinaculum, medial process of the calcaneus tuberosity, and intermuscular septum between itself and flexor hallucis brevis; the insertion is into the medial aspect of the proximal hallux phalanx, the collateral ligament of the proximal metatarsophalangeal joint, and the medial sesamoid bone [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have suggested that the pressure exerted on medial side of the foot and capsule of the irst metatarsophalangeal joint may cause development and progression of HV deformity [12,23]. Therefore, we aimed to determinate how much the amount of navicular drop would affect the HV angular severity and foot-speci ic health related quality of life in this study.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, the ND measurement is a practical technic for understanding the biomechanical relationship between the foot deformity and MLA structures [12]. The normal value of ND test was accepted 6 mm, value of 9 mm or more was considered high and values less than 6 mm were considered low [24,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the examinee sat in and maintained the subtalar neutral position, the examiner palpated the navicular tuberosity of the examinee, measured the height of the navicular bone using measurement equipment, and asked the examinee to stand on both feet. Then, the examiner measured again the height of the navicular bone and calculated the difference between the two measured values to obtain the result of the navicular drop test (NDT) 10 , 11 , 12 ) . In this study, a vernier height gauge (506-207; Mitutoyo, Kawasaki Japan) was used to measure NDT.…”
Section: Methodsmentioning
confidence: 99%